[1,3]-Dithiolo-[4,5-d][1,3-dithiole]-2,5-dione - Müller, Harald; Bourcet, Léa (Synthesis, 2021)
A safe, three-step reaction sequence to [1,3]-dithiolo-[4,5-d][1,3-dithiole]-2,5-dione starting from carbon disulfide is presented. Optimized reaction conditions, rigorous purification, and full characterization of all intermediates provide reproducibly a final product of superior quality with a melting point of 181 °C (dec.).
Keywords: 1,3,4,6-tetrathiapentalene-2,5-dione; thiapendione; 1,1,2,2-tetrathioethene; thermoelectricity; 2-oxo-1,3-dithiole-4,5-dithiolate; dmid